2012
DOI: 10.1016/j.bone.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the osteocyte lacunar–canalicular microenvironment due to estrogen deficiency

Abstract: While reduced estrogen levels have been shown to increase bone turnover and induce bone loss, there has been little analysis of the effects of diminished estrogen levels on the lacunar-canalicular porosity that houses the osteocytes. Alterations in the osteocyte lacunar-canalicular microenvironment may affect the osteocyte’s ability to sense and translate mechanical signals, possibly contributing to bone degradation during osteoporosis. To investigate whether reduced estrogen levels affect the osteocyte microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 65 publications
11
111
2
Order By: Relevance
“…Mechanisms of amplification within the osteocytic network facilitate the initiation and potentiation of intercellular signals between osteocytes. A recent study using a postmenopausal osteoporotic murine model identified a significant increase in lacunar-canalicular porosity in the ovariectomized animals compared with controls (58), and this dimensional increase in the pericellular space likely compromised the adhesion-mediated activation of osteocyte cell processes in the LCS. These estrogen-deficient animals developed a phenotype for exploring the loss of bone mass in postmenopausal women.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanisms of amplification within the osteocytic network facilitate the initiation and potentiation of intercellular signals between osteocytes. A recent study using a postmenopausal osteoporotic murine model identified a significant increase in lacunar-canalicular porosity in the ovariectomized animals compared with controls (58), and this dimensional increase in the pericellular space likely compromised the adhesion-mediated activation of osteocyte cell processes in the LCS. These estrogen-deficient animals developed a phenotype for exploring the loss of bone mass in postmenopausal women.…”
Section: Discussionmentioning
confidence: 98%
“…The low and high estimates are also consistent with Beno's work. In a more recent work, the number of canaliculi per lacuna was calculated from confocal microscopy images on a limited depth of 25 µm (Sharma et al, 2012). The authors reported about 85 primary and 387 secondary canaliculi per lacuna on rats' tibial metaphysis.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally two-dimensional imaging techniques, such as light microscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM) or transmission electron microscopy (TEM), have been proposed to visualize and quantify the LCN (Marotti et al, 1995;Kamioka et al, 2009;Lin and Xu, 2011;Sharma et al, 2012). Confocal microscopy can provide three-dimensional images, however, the limited penetration of light restricts the thickness of the visualized specimen and the spatial resolution is anisotropic (Sugawara et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been reported that osteocyte number density is 15 % higher in ↑ 119  132 µm 2 lacunar area (nonhuman primate, young  old) (Billings et al, 2012) = No significant difference in number of canaliculi (nonhuman primate, young  old) (Billings et al, 2012) ↑ More microdamage with increasing age (human, young < old) (Vashishth et al, 2000) Gender = Equal (human) (Vashishth et al, 2000;Qiu et al, 2002;Jordan et al, 2003) = Microdamage independent of gender (human) (Vashishth et al, 2000) ↑ 15 % more osteocytes (healthy males < healthy females) (Mullender et al, 2005) Osteoporosis (OP)/Oestrogen deficiency ↑ Lacunae 17,100  12,900/mm 3 (women and men pooled, control  OP) (Mullender et al, 1996) 610  508/mm 2 (women and men pooled, control  OP) (Jordan et al, 2003) Osteocytes 13,300  10,500/mm 3 (women and men pooled , control  OP) (Mullender et al, 1996) (Sharma et al, 2012) Alterations in the osteocyte lacuna number density (sheep, iliac crest, control <=> OP model) (Zarrinkalam et al, 2012) ↓ Lacunae 206  134/mm 2 (Postmenopausal women, healthy  OP) (Qiu et al, 2003) 21 % less (sheep, lumbar spine, control > OP model) (Zarrinkalam et al, 2012) Osteocytes 249  214/mm 2 (sheep, iliac crest, control  OP model) (Zarrinkalam et al, 2012) 271  223/mm 2 (women, healthy  OP), 223  199/mm 2 (men, healthy  OP), (Mullender et al, 2005) 188  125/mm 2 (postmenopausal women, healthy <=> OP) (Qiu et al, 2003) Osteomalacia ↑ Larger lacunae (mice, healthy model < osteomalacia model) = No difference in number of osteocyte processes (human , healthy  osteomalacia) (Knothe Tate et al, 2004) ↓ Lacunae less oriented (mice, control  osteomalacia model) (Knothe Tate et al, 2004;Jaiprakash et al, 2012) = Orientation preserved in OA (human, healthy  OA) (Knothe Tate et al, 2004) ↑ Increased osteocyte apoptosis in OA (human) (Wong et al, 1987) ↑ More microdamage suggested for patients with OA (human, healthy < OA) (Fazzalari et al, 1998) Diabetes ↓ 10.1 % fewer lacunae (mice, control > diabetes model) …”
Section: Gendermentioning
confidence: 99%
“…Recent finite element and fluid-structure interaction models have used relatively low resolution image data and made a priori assumptions about the actual dimensions of the ON&LCN, such as the pericellular space (PCS) between the ON&LCN (Verbruggen et al, 2012;Verbruggen et al, 2014). One perspective on osteoporosis is that it is a failure of bone's adaptation to functional loading, that is, a failure of its mechanotransduction and/or mechanosensation capacity (Sharma et al, 2012;Ciani et al, 2014). Two mechanisms, direct response to matrix deformation and indirect response to fluid flow alteration have been suggested as possible pathways for mechanotransduction.…”
Section: Introductionmentioning
confidence: 99%